1997
DOI: 10.1016/s1063-4584(97)80023-4
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of adenovirally transduced allogeneic chondrocytes into articular cartilage defects in vivo

Abstract: Gene transfer to chondrocytes followed by intra-articular transplantation may allow for functional modulation of chondrocyte biology and enhanced repair of damaged articular cartilage. We chose to examine the loss of chondrocytes transduced with a recombinant adenovirus containing the gene for Escherichia coli beta-galactosidase (Ad.RSVntlacZ), followed by transplantation into deep and shallow articular cartilage defects using New Zealand White rabbits as an animal model. A type I collagen matrix was used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 13 publications
3
57
0
2
Order By: Relevance
“…During the cartilage healing process, 4 weeks of protein expression may be insufficient to generate mature repaired tissue. Our results, compared with those generated by MDC or chondrocyte transplantation (16,47,48), indicate that the better survival of transplanted MDSCs led to significantly enhanced and prolonged LacZ transgene expression within the cartilage lesions.…”
Section: Bmp-4 and Mdscs In Cartilage Repairmentioning
confidence: 52%
“…During the cartilage healing process, 4 weeks of protein expression may be insufficient to generate mature repaired tissue. Our results, compared with those generated by MDC or chondrocyte transplantation (16,47,48), indicate that the better survival of transplanted MDSCs led to significantly enhanced and prolonged LacZ transgene expression within the cartilage lesions.…”
Section: Bmp-4 and Mdscs In Cartilage Repairmentioning
confidence: 52%
“…Similar results have been obtained with chondrocyte-seeded collagen type I matrices following genetic modification of the cells with adenovirus. 63,64 More recently it was found that transfected chondrocytes incorporated into alginate spheres and implanted into osteochondral defects in rabbit knees would express detectable levels of activity from marker genes from plasmid DNA for as long as 32 days. 45 Together, these studies confirm the feasibility of using chondrocytes as a means of ex vivo gene transfer to cartilage lesions and that prolonged expression of a transgene in vivo (ie X2 weeks) is feasible using commonly available vectors and three-dimensional supports.…”
Section: Chondrocytes As Targets For Gene Deliverymentioning
confidence: 99%
“…These cells are susceptible to adenoviral, and retroviral transduction, and ex vivo gene transfer to cartilage has been achieved with both of these vectors (44,45). Direct injection of adenoviral vectors into normal joints does not transduce chondrocytes, but neutral liposomes containing the hemaglutinizing virus of Japan can apparently diffuse into articular cartilage and deliver genes to chondrocytes in vivo (46).…”
Section: Other Arthritides and Related Disordersmentioning
confidence: 99%